(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
The ancient Indian science of life, Ayurveda has successfully thrived since its inception till today due to its strong foundation in the form of basic principle. Ayurveda consists of not only science but also the philosophy. Ayurveda has evolved with the inputs from the then existing philosophical thoughts and has modified so as to suit its purpose. Philosophy in Ayurveda indicates the love for truth and truth in Ayurveda is the pure existence of a person. To know a science properly one should have the thorough knowledge of all the fundaments. Acharyas also states that one who wants to comprehend the science completely needs to take the help of the basic science which existed during the time when Ayurveda was evolved. There are many fundaments in Ayurvedic literature till to be proved and to know its practical utility. Prakriti samasamaveta and Vikriti visamasamaveta are the two siddhanta given by Acharya Charak while describing relation between Rasa-Dravya and Dosha-Vyadhi. This study is carried out with a view to know the applicability of this siddhanta in treatment purpose.